2012
DOI: 10.1002/bem.21732
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exposure to 50 Hz ELF‐EMF alters the cisplatin‐induced oxidative response in AT478 murine squamous cell carcinoma cells

Abstract: The aim of this study was to assess the influence of cisplatin and an extremely low frequency electromagnetic field (ELF-EMF) on antioxidant enzyme activity and the lipid peroxidation ratio, as well as the level of DNA damage and reactive oxygen species (ROS) production in AT478 carcinoma cells. Cells were cultured for 24 and 72 h in culture medium with cisplatin. Additionally, the cells were irradiated with 50 Hz/1 mT ELF-EMF for 16 min using a solenoid as a source of the ELF-EMF. The amount of ROS, superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 39 publications
3
28
0
2
Order By: Relevance
“…These results showed that cisplatin decreases the antioxidant power, so that it increases the peroxidation damages of the body, whose results were fairly in accorded with some studies' (Sahu BD et al, 2011;Buldak RJ et al, 2012;Gupta RK et al, 2013;Zhao YM et al, 2014). In this experiment, the oxidative stress indices in the pu-erh tea related groups changed to some extent compared to the cisplatin group, including the activities of SOD and GSH-PX and the levels of GSH were increased, while the levels of MDA were decreased.…”
Section: Discussionsupporting
confidence: 87%
“…These results showed that cisplatin decreases the antioxidant power, so that it increases the peroxidation damages of the body, whose results were fairly in accorded with some studies' (Sahu BD et al, 2011;Buldak RJ et al, 2012;Gupta RK et al, 2013;Zhao YM et al, 2014). In this experiment, the oxidative stress indices in the pu-erh tea related groups changed to some extent compared to the cisplatin group, including the activities of SOD and GSH-PX and the levels of GSH were increased, while the levels of MDA were decreased.…”
Section: Discussionsupporting
confidence: 87%
“…Buldak et al. found not only an increased SOD activity but also an increased GPx activity and a reduced lipid peroxidation in AT478 exposed to ELF‐EMF of 50 Hz and 1 mT up to 72 H . Cellular adaptation to ELF‐EMF was also noted in pheochromocytoma‐derived cells exposed to 50 Hz and 0.1–1 mT, increased ROS production and decreased CAT activity were observed after 30 Min of exposure, but an opposite tendency for these parameters was observed after chronic exposure of 7 days .…”
Section: Resultsmentioning
confidence: 95%
“…Falone et al observed higher GSH levels, but higher GPx, glutathione S-transferase, and γ -glutamylcysteine synthetase activity and higher Glut expression in neuroblastoma cells after 50 Hz and 1 mT of exposure for 96 H [57]. Buldak et al found not only an increased SOD activity but also an increased GPx activity and a reduced lipid peroxidation in AT478 exposed to ELF-EMF of 50 Hz and 1 mT up to 72 H [58]. Cellular adaptation to ELF-EMF was also noted in pheochromocytoma-derived cells exposed to 50 Hz and 0.1-1 mT, increased ROS production and decreased CAT activity were observed after 30 Min of exposure, but an opposite tendency for these parameters was observed after chronic exposure of 7 days [47].…”
Section: Figmentioning
confidence: 99%
“…Data generated from several epidemiological studies on populations occupationally exposed to ELF-MF have been interpreted as indicative of increased risk and incidence of some diseases, including leukemia [Kheifets et al, 2009], neurodegenerative diseases [Park et al, 2005], and some brain tumors [Repacholi and Greenebaum, 1999]. In vitro studies reported that ELF-MF could affect antioxidant activities [Wolf et al, 2005;Polaniak et al, 2010], cell growth [Wolf et al, 2005;Sulpizio et al, 2011], and cytoskeletal organization [Sulpizio et al, 2011] and could induce DNA damage through the action of free radical species [Wolf et al, 2005;Vijayalaxmi and Prihoda, 2009;Bułdak et al, 2012;Luukkonen et al, 2014]. Recently, several papers evaluated positive effects of ELF-MF on cytokine profiles driving transition from a chronic pro-inflammatory state to an anti-inflammatory state associated with the healing process [Costin et al, 2012;Pesce et al, 2013;Saliev et al, 2014] and neurodegenerative diseases [Mattsson and Simk o, 2012].…”
Section: Introductionmentioning
confidence: 99%